2009
DOI: 10.1111/j.1528-1167.2009.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of epilepsy in the United States

Abstract: ; zEpilepsy Foundation of America, Landover, Maryland, U.S.A.; and xIndiana University School of Nursing, Indianapolis, Indiana, U.S.A. SUMMARYPurpose: To assess differences in medical care expenditures and informal care received for adults and children by individuals' self-reported epilepsy status and to estimate the total economic impact of epilepsy in the United States. Methods: Pooled medical expenditure panel survey data from 1996-2004 were used. Children's regression analyses were adjusted for race, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 27 publications
2
82
0
Order By: Relevance
“…12 This study also found that for both children and adults, patients with epilepsy were more likely to be uninsured or only have public insurance, which may pose a serious societal burden given the substantial total costs of treating epilepsy. In another survey-based analysis of adult patients, the projected annual cost of epilepsy to society was US $12.5 billion, including direct costs (e.g., medical services, diagnostic procedures, emergency room visits, treatment) and indirect costs (e.g., lost wages), adjusted to 1995 prices.…”
Section: Model Structure and Inputsmentioning
confidence: 75%
“…12 This study also found that for both children and adults, patients with epilepsy were more likely to be uninsured or only have public insurance, which may pose a serious societal burden given the substantial total costs of treating epilepsy. In another survey-based analysis of adult patients, the projected annual cost of epilepsy to society was US $12.5 billion, including direct costs (e.g., medical services, diagnostic procedures, emergency room visits, treatment) and indirect costs (e.g., lost wages), adjusted to 1995 prices.…”
Section: Model Structure and Inputsmentioning
confidence: 75%
“…One article estimated direct medical costs in both children and adults in the year 2004, but did not estimate full indirect costs. 30 Assuming static disease prevalence from 2004 to 2014, adjusting to 2014 dollars, and using the Bureau of Labor Statistics medical price index, the direct medical costs of epilepsy for 2014 are estimated at $13.4 billion. 31 However, indirect costs for epilepsy patients are quite substantial, accounting for 66% of total cost for adults, and 20% of total cost for children.…”
Section: Epilepsymentioning
confidence: 99%
“…[1][2][3][4] Several initiatives have demonstrated such reductions may be possible for both adults and children with epilepsy. [5][6][7][8] People with epilepsy at high risk for frequent ED visits are an ideal target group for enrollment in programs to enhance outpatient care, because frequent ED use indicates poor access to care and/or poor disease control.…”
Section: Introductionmentioning
confidence: 99%